Effect Of Net Income And Operating Cash Flow On Cash Dividends - Sherly Rinjani; Uswatun Hasanah (Pusat P2M Politeknik Negeri Batam, 2019)
In invested, investors are more interested to shared profits at the form of cash dividends. The factor that can determine the amount of cash dividends that companies shared to investors are financial condition of the company which consists of net income and operating cash flow. The objective of this research is to determine the influence of net income and operating cash flows on cash dividends. The population of this research was pharmaceutical sub-sector manufacturing company on the Indonesia Stock Exchange (IDX) 2013-2018 Period. The sampling technique used in this research is purposive sampling method, and five companies have conform of that criteria sampling. This research used multiple linear regression analysis with IBM SPSS 23 software.The result of this research showed that (1) net income has influence on cash dividends (2) operating cash flow has influence on cash dividends.